Assessment of genetic resistance and abomasal tissues expression of Yichang white goat experimentally challenge with Haemonchus contortus infection (Progressive Agriculture, 2019)
Our previous association study revealed the mutation in candidate immune genes (NOD1 & NLRP9) was significantly associated with FEC of Haemonchus contortus infection in Yichang white goats, but the relative expression of mRNA of those genes associated with resistance to H. contortus was not investigated. Aim of the current experiment was to evaluate the susceptible and resistant individuals to nematode infection within the population of Yichang white goat (YWG) and assess the differential level of mRNA expression of those candidate genes in the abomasal tissues of susceptible and resistant goats. Fecal egg count (FEC) was determined using a modified McMaster technique, and the hematological parameter was measured by Mindray auto hematology analyzer. Phenotype data were collected and analyzed using a generalized linear model with SAS statistical program. Field investigate revealed that the prevalence (76%) with maxium parasite load (734.34±84.21epg) of H. contortus occurred in August within the experimental flock  FEC in resistant group (103.38±1.20epg) and susceptible group (1180.25±43.53epg) group  demonstrated the presence of  two distinct goat populations within this breed. Four resistant and four susceptible goats were selected from each group. The parasite infection was established by artificially challenge with 5000 infective L3 larvae of H. contortus. Abomasal tissues were collected from all experimental goats after 42 days of post-infection. FEC, Body weight, packed cell volume, and hemoglobin value were significantly different (P < 0.01) between resistant and susceptible group of goats. Quantitative real-time PCR in abomasal tissues revealed that the expression level of mRNA for NOD1 (P < 0.00001), IFNG (P < 0.0001), NLRP9, TLR8, IL32, (P < 0.001) and IGF1 (P < 0.01) was higher in resistant goat compared to susceptible, except SFTPA1. These findings revealed the presence of genetic resistant individuals to H. contortus within the goat breed and expression of NOD1 and  NLRP9 genes proved the positive finding of our previous study. Presence of genetic resistant individuals in Yichang white goat YWG breed could be a good candidate for selective breeding and highly expressed genes related to resistant could be used as biomarkers to develop H. contortus resistant goat population.Progressive Agriculture 30 (2): 194-208, 2019